13th annual College of Veterinary Medicine and Biomedical Sciences research day scientific proceedings - Colorado State University. College of Veterinary Medicine and Biomedical Sciences, author (Colorado State University. Libraries, 2012)
Includes the Pfizer Research Award winner and abstracts only of the oral sessions and posters.
13th annual CVMBS research day scientific proceedings
CVMBS research day 2012
Held in the Hilton Hotel on January 28, 2012, Fort Collins, Colorado.
Keywords: Veterinary medicine -- Congresses; Veterinary medicine -- Research -- Congresses